2021
DOI: 10.24018/ejfood.2021.3.6.427
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Risk Coping Strategies Among Catfish Farmers in Ikorodu Division, Lagos State, Nigeria

Abstract: The aim of this study was to analyse the risk coping strategies among catfish farmers in Ikorodu division of Lagos State, Nigeria. Primary data were obtained from 100 catfish farmers with the aid of a pre-tested questionnaire and focus group discussion using multistage sampling technique. Descriptive statistics and multivariate probit regression model were employed for data analysis. Results revealed that majority (68.1%) of the respondent were male with a mean age of 41 years and a mean stock size of 1130. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(18 reference statements)
2
0
0
Order By: Relevance
“…Table 1 shows that most (68.12 percent) of the respondents were males while the remaining 31.88% were females. The result on sex agrees with Aminu et al [9] who reported that 68.1 percent of catfish farmers in Lagos are males.…”
Section: Sex Of the Respondentssupporting
confidence: 91%
See 1 more Smart Citation
“…Table 1 shows that most (68.12 percent) of the respondents were males while the remaining 31.88% were females. The result on sex agrees with Aminu et al [9] who reported that 68.1 percent of catfish farmers in Lagos are males.…”
Section: Sex Of the Respondentssupporting
confidence: 91%
“…The reported mean age among catfish farmers in the study area was 48 years. This is similar to Aminu et al [9] who reported a mean age of 41 years among fish farmers in Lagos. Regardless of the impressive percentage of youth (23.12%) participation in catfish production, the reported mean age shows an aging farming population in the catfish enterprise, and the sector may face challenges in the future due to the aging of the current generation of catfish farmers.…”
Section: Age Of the Respondentssupporting
confidence: 91%